2015
DOI: 10.3389/fnhum.2015.00136
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the COMT Val158Met polymorphism on resting-state EEG power

Abstract: The catechol-O-methyltransferase (COMT) Val158Met polymorphism impacts cortical dopamine (DA) levels and may influence cortical electrical activity in the human brain. This study investigated whether COMT genotype influences resting-state electroencephalogram (EEG) power in the frontal, parietal and midline regions in healthy volunteers. EEG recordings were conducted in the resting-state in 13 postmenopausal healthy woman carriers of the Val/Val genotype and 11 with the Met/Met genotype. The resting EEG spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Although polymorphisms of COMT and DRD4 had been linked to EEG phenotypes (Loo et al 2010 ; Solís-Ortiz et al 2015 ), these potential links had not yet been investigated within tasks examining the neurophysiological indices of frontostriatal and parietal attentional networks. Our study aimed to investigate the relationship between COMT and DRD4 polymorphisms and ICA source-resolved brain activity during a cognitive control task, and our findings suggest higher genetic penetrance for IC-derived EEG measures of cognitive control than traditional channel based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Although polymorphisms of COMT and DRD4 had been linked to EEG phenotypes (Loo et al 2010 ; Solís-Ortiz et al 2015 ), these potential links had not yet been investigated within tasks examining the neurophysiological indices of frontostriatal and parietal attentional networks. Our study aimed to investigate the relationship between COMT and DRD4 polymorphisms and ICA source-resolved brain activity during a cognitive control task, and our findings suggest higher genetic penetrance for IC-derived EEG measures of cognitive control than traditional channel based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs in the DAT1 transporter protein gene alter the recapture of dopamine[ 95 ], which have been associated with impulsivity and increased food intake[ 96 , 97 ]. A reduced COMT activity in the Val158Met polymorphism affects the degradation of dopamine and other catecholamines (epinephrine, norepinephrine) causing higher dopamine synaptic levels[ 98 , 99 ]. Stein et al[ 100 ] have proposed that Met / Met carriers be identified as “worriers” whereas the Val / Val carriers were known as “warriors” in response to stress resistance.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Little is known about the genetics underlying EEG traits or pharmacologically modulated EEG, but twin studies show that heritability of resting EEG oscillations is substantial (Stassen et al 1987), particularly for PAF (Posthuma et al 2001;Smit et al 2005Smit et al , 2006 and -band oscillations with 80-90% heritability estimates (Van Beijsterveldt & van Baal 2002;Van Beijsterveldt et al 1996). The COMT polymorphism contributes to individual differences in brain oscillations, with Val homozygotes exhibiting reduced 2 and PAF compared to Met/Met carriers (Bodenmann et al 2009a;Enoch et al 2003), who exhibited greater delta, theta and beta (Solis-Ortiz et al 2015).…”
mentioning
confidence: 99%